Fatores críticos da competitividade da cadeia produtiva do ovo no estado de São Paulo - Kakimoto, Sergio Kenji (Universidade Federal de São Carlos, 2011)
Brazil is the second greatest world producer of eggs; the production value of the egg ranks 13th among the agricultural products in the country. The Brazilian export of eggs is still incipient, but, the production potential is great since there are positive points such the climate, space, input availability and technology. It was aimed through this work to report the functioning, to investigate the role of the several economic agents and identify the critical determinants of the competitiveness of the production chain of the egg in the state of São Paulo. The methodology utilized was done through the evaluation of the competitiveness drivers with the aid of questionnaires, ascribing values of very unfavorable, neutral, favorable and very favorable to a series of sub-factors. Seven competitiveness drivers of greatest impact in the sector were selected, namely: firm management, technology, inputs, market structure, chain governance, infrastructure and institutional setting. Out of these factors were ascribed sub-factors which were evaluated and advised the survey and the analysis of the results. By means of the rapid appraisal methodology were interviewed key-agents of the chain as well obtained data in secondary sources. The interviews were directed towards the agents of the production chain link and agents of the sectoral organization of the state of São Paulo. It follows that the drivers who contribute towards the competitiveness of the production chain of eggs were both technology and firm management which have the control degree by the firm while the others remain neutral, not contributing to competitiveness. The cost of inputs, mainly the corn and the freight value, were sub-factors unfavorable to the production chain.
Keywords: Cadeia de suprimentos; Avicultura; Agribusiness; Ovos - comercialização; Aves poedeiras - criação; Poultry farming; Agribusiness; Egg commercialization; Eggs; Laying hens; ENGENHARIAS::ENGENHARIA DE PRODUCAO